Beyond Play Your Process - Game Design and Business Process Model: A Rapid Review - Lima, Caroline da Conceição; Xexéo, Geraldo; Classe, Tadeu Moreira de (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Digital games have been increasingly explored beyond entertainment, including business process modeling. However, assessing how process models have been used in digital game development is necessary. Objective: This article presents a rapid review to identify and evaluate studies that implement business process models in digital games. Methodology or Steps: The review covers studies from Jan 2018 to Mar 2024, complementing a 2017 systematic review. The snowballing technique was applied to the paper “The Play Your Process Method for Business Process-Based Digital Game Design”. Results: After filtering 151 articles, 20 were fully analyzed. Findings show that 13 studies use process models for game development, nearly five times more than the last systematic mapping.